2017
DOI: 10.1080/10641963.2017.1291660
|View full text |Cite
|
Sign up to set email alerts
|

Association of the −344T/C polymorphism in aldosterone synthase gene promoter with left ventricular structure in Chinese Han: A meta-analysis

Abstract: No consensus view has been published on the relationship between the aldosterone synthase gene (CYP11B2) -344C/T polymorphism and left ventricular hypertrophy (LVH) in Chinese Han. We undertook a meta-analysis to investigate the potential association of this polymorphism and left ventricular structure-related phenotypes, including left ventricular mass (LVM), left ventricular mass index (LVMI), left ventricular end systolic diameter (LVESD), left ventricular end diastolic dimension (LVEDD), left ventricular po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…indicated that −344C/T polymorphism might be associated with CAD in Caucasian and Asian populations. 8 However, Mishra et al. 26 indicated that the −344C/T polymorphism in CYP11B2 is not correlated with CAD or left ventricular hypertrophy in an Indian population, although that study did not involve stratification by sex.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…indicated that −344C/T polymorphism might be associated with CAD in Caucasian and Asian populations. 8 However, Mishra et al. 26 indicated that the −344C/T polymorphism in CYP11B2 is not correlated with CAD or left ventricular hypertrophy in an Indian population, although that study did not involve stratification by sex.…”
Section: Discussionmentioning
confidence: 98%
“…25 In a metaanalysis, Yin et al indicated that À344C/ T polymorphism might be associated with CAD in Caucasian and Asian populations. 8 However, Mishra et al 26 indicated that the À344C/T polymorphism in CYP11B2 is not correlated with CAD or left ventricular hypertrophy in an Indian population, although that study did not involve stratification by sex. In addition, a prospective study of healthy British men discovered that the À344C/T variant is not associated with cardiovascular risk.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations